TRADISI DAN BUDAYA TOLERANSI DALAM TINJAUAN SEJARAH DI ACEH - Nurlaila, Nurlaila (Prodi Studi Agama-Agama, 2022)
The discussion of tolerance has become a hot topic discussed in various studies, both in the form of writing and verbally through various dialogues and forums. Tolerance is an easy topic to discuss in sharing forums, but in its realization and application there is still a lot to learn. The problem of tolerance is a test in itself in society, because although there are many scientific studies that discuss the necessity and obligation of a culture of tolerance in society. But in reality tolerance is always a problem in realizing it. This sometimes becomes difficult in its realization because it is found that there are still many citizens, groups or even certain cultures who are intolerant in various ways. Aceh, an area that applies Islamic law in Indonesia, is a test in itself in implementing a culture of tolerance in Aceh. There were several cases that caused Aceh to become intolerant, starting from the DI/TII rebellion in 1953 which was intolerant of Indonesia, the displacement of other ethnic groups during GAM's burning of houses of worship in Aceh and various other cases that indicated that Aceh was intolerant. Seeing this reality, this study wants to see another angle on the problem of tolerance in Aceh. The author sees from the perspective of culture and history, Aceh is very tolerant in religious matters. So that in the course of Aceh's history they can live, do business, diplomacy and discuss with various religions.AbstrakPembahsan tentang toleransi menjadi topik yang hangat di bicarakan dalam berbagai kajian baik di berupa tulisan, maupun pembicaraan secara lisan lewat bergai dialog dan forum. Toleransi menjadi topik yang mudah untuk di bahas dalam berbagi forum namun dalam perwujudan dan aplikasinya masih harus terus banyak belajar. Masalah toleransi menjadi ujian tersendiri dalam masyarakat, karena meski banyak kajian ilmiah yang membahas harus, perlu dan wajibnya budaya toleransi dalam bermasyarakat. Namun kenyataannya toleransi selalu terjadi masalah dalam mewujudkan. Hal tersebut kadang menjadi susah dalam perwujudannya karena didapati masih banyak warga, kelompok atau bahkan budaya tertentu yang bersikap intoleran dalam berbahai hal. Aceh sebuah daerah yang menerapkan syariat Islam di Indonesia menjadi ujian tersendiri dalam menerapakan budaya toleransi di Aceh. Ada beberapa kasus yang menyebabkan Aceh menjadi in toleran mulai dari pemberontaka DI/TII tahun 1953 yang tidak toleran dengan Inonesia, pengusian etnis lain pada saat GAM pembak aran rumah ibadah di Aceh dan berbagai kasu lain yang mengindikasikan Aceh intoleran. Melihat realitas tersebut kajian ini ingin melihat sudut lain dari permasalah toleransi di Aceh. Penulis melihat dari kaca mata budaya dan sejarah dulu, Aceh sangat toleran dalam masalah agama. Sehingga dalam perjalanan sejarah Aceh bisa hidup, berbisnis, berdiplomasi dan berdiskusi dengan berbagai Agama.